PENGARUH TINGKAT KECUKUPAN MODAL, TINGKAT LIKUIDITAS DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS DENGAN RISIKO KREDIT SEBAGAI VARIABEL MODERASI - Apriyanti, Metha Dwi (Jurnal Bisnis Manajemen dan Akuntansi, 2026)
This study examines the effect of capital adequacy, liquidity, and operational efficiency on profitability of conventional banks listed on the Indonesia Stock Exchange during the period 2019–2024, with credit risk as a moderating variable. Using a quantitative approach and purposive sampling, the sample consists of 22 banks. Panel data regression analysis was conducted using Eviews 12. The results show that, partially, capital adequacy and operational efficiency do not affect profitability, while liquidity positively influences profitability. Simultaneously, capital adequacy, liquidity, and operational efficiency all affect profitability. However, credit risk only moderates the relationship between these variables and profitability.